Profile of calories and nutrients intake in a Brazilian multicenter study of nulliparous women - Miele, Maria J. O.; Souza, Renato T.; Calderon, Iracema M. [UNESP]; Feitosa, Francisco E.; Leite, Débora F.; Rocha Filho, Edilberto A.; Vettorazzi, Janete; Mayrink, Jussara; Vieira, Matias C.; Pacagnella, Rodolfo C.; Cecatti, José G. (Wiley, 2021)
Objective: To assess the calorie intake and nutritional content of the maternal diet in regions with different culinary traditions and typical foods, and to understand the nutritional profile so as to provide information about the consumption of this population and promote maternal and perinatal health. Methods: From a cohort of 1145 pregnant women with diverse socio-backgrounds we analyzed the dietary characteristics profile according to three guidelines and compared the differences between regions of Brazil. Results: Women from the northeast had the lowest level of income, occupation, education, and age (P < 0.001). Intakes of unprocessed/minimally processed foods and processed foods were more prevalent in women from the northeast than in southern/southeastern women (P < 0.001). The consumption of dairy products and vegetables was less than the recommended intake, with lower intake in southern/southeastern women (P < 0.001). This study showed a lower consumption of dairy and vegetables, with a shortfall of vitamins K and D, iron, calcium, folate, magnesium, and chromium from natural and fortified foods. We observed a greater consumption of unprocessed or minimally processed food in women from the northeast of Brazil. Conclusion: Our findings indicate the importance of differentiating the source of calorie intake between regional nutritional guidance and the diversity of local cuisine.
Keywords: energy intake; food consumption; maternal nutrition; pregnancy; ultra-processed foods